Classification of collaborative behavior from free text interactions. (January 2018) - Berdun, Franco D.; Armentano, Marcelo G.; Berdun, Luis; Mineo, Martín
Graphical abstract: Abstract: In a computer-supported collaborative work (CSCW) environment, a group of people can work together to fulfill a given assignment. In this context, collaborative problems might naturally arise. The detection of these problems is extremely important for teachers or team leaders to help the team members to improve their collaborative skills and the resolution of the collaboration problems. The observation and analysis of the interaction process of several groups is a time-consuming and difficult task for any teacher or team leader. In this article, we propose a multi-phase classification approach to automatically classify free text observed form the chat of a CSCW environment into different collaborative categories of behavior. We obtained promising results that can be used to help teachers or team leaders with the interaction process analysis in order to focus only in the resolution's actions of the problems that might arise.